A Meta analysis of research on private finance initiative (PFI) or public private partnership (PPP) - Ismail, Suhaiza (2011)
Purpose: The study aims to evaluate systematically the key characteristics of PFI/PPP research in top public-sector journals and to offer suggestions on the future direction of research on PFI/PPP. Methodology: A qualitative meta-analysis method is used to analyse 134 PFI/PPP published papers from twenty nine selected public sector journals from 1992 to 2009. Findings: There is evidence of a growing trend in the number of PFI/PPP literature since its inception. The extant research that has used various methods were contributed by authors from diverse countries, particularly the United Kingdom. Past literature also mostly focuses on specific PFI/PPP issues such as risk, value for money, and performance of PFI/PPP, although other issues have been investigated from time to time. Research limitations: This present comprehensive content analysis of prior research on PFI/PPP only considers research published in public sector journals and not literature from all other relevant fields of knowledge where PFI/PPP is one of the important areas of research. Originality/value: This study offers some insights into the trends of PFI/PPP literature in top-ranking public sector journals.